Pelumasan Rantai Otomatis Pada Roller Chain Conveyor Menggunakan Metode Regresi Linear - Irwanda Adhi Firmantara; M. Hannats Hanafi Ichsan; Barlian Henryranu Prasetio (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
At this time the chain lubrication which is conducted by operator on conveyor machine spent a lot of time because of the number of conveyor machine. The operator must lubricate a lot of conveyor chain so that the working hours become inefficient. To solve the problem then made an automatic lubrication system. The purpose of this research so that operators can manage the lubrication time on conveyor chain and then the operator can do their job. This automatic lubrication system works based on current level obtained by using ACS712 current sensor which is then calculated using linear regression method in arduino UNO to get the prediction value of lubrication duration. This value is used to activate wind solenoid relay, oil pump relay and oil solenoid relay. After the prediction of lubrication time has been fulfilled by all relays, the system re-measure the current for further lubrication. Proximity sensor is useful when the system is active, the oil pump relay is also active to deliver oil from the oil pump to the oil solenoid. This research uses linear regression method. The solution of this method is to use the current parameter as the independent variable (X) and the time of manual lubrication as the dependent variable (Y) so that the predicted value of the dependent variable (Å¶) can be calculated as the duration of the automatic lubrication time. By using this method when the current reached the value of 3.88 A obtained the prediction value of the duration of automatic lubrication for 210 seconds. With 2.21% value of error between manual lubrication and automatic lubrication, the predicted value is not much different from manual lubrication time. The the difference predicted value is not too much between manual lubrication time and automatic lubrication system.